High Research Productivity During Orthopaedic Surgery Residency May Be Predicted by Number of Publications as a Medical Student - Connor Donley, MD; Matthew McCrosson, BS; Sri Prahad, BS; Collier Campbell, MD; Fei Zhao, BS; Narcy Amireddy, BS; Michael Johnson, MD, FAOA (JBJS Open Access, 2024)
Introduction:. Orthopaedic applicants have increased the average number of publications on their residency application to compete with the growing competitiveness of the field. The purpose of this study was to assess whether research productivity before orthopaedic residency and caliber of one's institution is correlated with academic productivity during residency. Methods:. Scopus was used to extract publication metrics. Quantity and quality (how often the publications were cited) were analyzed at 2 different time periods: before and during residency. All subjects in the study had graduated an ACGME-accredited orthopaedic surgery residency in 2021. Military residents, international medical graduates, and residents not listed on their department's website were excluded. Residents were categorized as both high (≥2 publications) or low (<2 publications) publishers according to their pre-residency publications. They were also categorized based on their program's Jones et al. research productivity ranking. Results:. For the 758 residents, the median number of publications was 0 (Interquartile Range [IQR]: 0-2) and 3 (IQR: 1-6) before and during residency, respectively. High publishing medical students had more publications during training than low publishers (6 [IQR: 3-14] and 2 [IQR: 1-4], p < 0.001). Residents at higher ranked programs also had more publications (4 [IQR: 2-9] and 2 [IQR: 0-4], p < 0.001). High publishing students now training at lower ranked institutions had more publications during residency than low publishers who trained at more productive institutions (4 [IQR: 1-9] and 3 [IQR: 1-6], p < 0.001). Conclusion:. Having 2 or more publications before residency is correlated with an increased number of publications during residency. While attending a higher academically productive program is associated with increased resident publications, a high publishing medical student would be expected to have more publications during residency than a low publishing student, regardless of program rank. Notably, most matched applicants continue to have zero publications before matriculation.